Administrasi Publik Berbasis Media Digital “Klinik Investasi” dalam Perspektif Maqasid Syariah - Zainil Ghulam; Rio Febriannur Rachman (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2026)
This study examines digital-based public administration practices through the Klinik Investasi program in Surabaya from the perspectives of public administration and maqāṣid al-sharī‘ah. The program represents an innovation in licensing and investment services by utilizing multiple digital platforms to enhance efficiency, transparency, and citizen participation. This research employs a qualitative approach using directed content analysis, combining digital content data with in-depth interviews. The findings indicate that the Klinik Investasi is not merely a technological innovation but a structural transformation toward a more responsive, inclusive, and citizen-centered model of digital governance. From the maqāṣid al-sharī‘ah perspective, the program contributes to public welfare by safeguarding economic interests, enhancing public knowledge, and expanding equitable access to services. Furthermore, the program aligns with the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice, and Strong Institutions). Therefore, the Klinik Investasi can be understood as a best practice model that integrates digital innovation, normative values, and sustainable development within a comprehensive public service framework.